2015
DOI: 10.1371/journal.pone.0129113
|View full text |Cite
|
Sign up to set email alerts
|

The Taxonomic Status of Mazama bricenii and the Significance of the Táchira Depression for Mammalian Endemism in the Cordillera de Mérida, Venezuela

Abstract: We studied the taxonomy and biogeography of Mazama bricenii, a brocket deer classified as Vulnerable by the IUCN, drawing on qualitative and quantitative morphology and sequences of the mitochondrial cytochrome-b gene. We used Ecological Niche Modeling (ENM) to evaluate the hypothesis that M. bricenii of the Venezuelan Cordillera de Mérida (CM) might have become isolated from populations of its putative sister species, Mazama rufina, in the Colombian Cordillera Oriental (CO). This hypothesis assumes that warm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 67 publications
(87 reference statements)
2
45
0
2
Order By: Relevance
“…M. rufina was considered absent from the eastern mountain range and still its northern distribution is not well known (Lizcano and Alvarez 2008), while M. bricenii is presumed to occur in northern Colombia in areas such as Tamá NNP (Lizcano et al 2010). The classification and identification of M. bricenii and M. rufina have been subject to recent debate (e. g., Solari et al 2013;Gutiérrez et al 2015), however, according to available descriptions for both species (Barrio 2010;Gutiérrez et al 2015), and taxon validity (Gutiérrez et al 2015), our records correspond to M. rufina. We therefore obtained multiple records of M. rufina between 350 and 3,450 m, in areas of tropical forest and Páramo (i. e., Páramo del Tamá and Páramo de Santa Isabel) near the border with Venezuela, indicating that the species is mostly nocturnal and solitary, adding some lights on the scarce knowledge of this species ecology (Lizcano and Alvarez 2008;Merino and Rossi 2010).…”
Section: Discussionmentioning
confidence: 83%
“…M. rufina was considered absent from the eastern mountain range and still its northern distribution is not well known (Lizcano and Alvarez 2008), while M. bricenii is presumed to occur in northern Colombia in areas such as Tamá NNP (Lizcano et al 2010). The classification and identification of M. bricenii and M. rufina have been subject to recent debate (e. g., Solari et al 2013;Gutiérrez et al 2015), however, according to available descriptions for both species (Barrio 2010;Gutiérrez et al 2015), and taxon validity (Gutiérrez et al 2015), our records correspond to M. rufina. We therefore obtained multiple records of M. rufina between 350 and 3,450 m, in areas of tropical forest and Páramo (i. e., Páramo del Tamá and Páramo de Santa Isabel) near the border with Venezuela, indicating that the species is mostly nocturnal and solitary, adding some lights on the scarce knowledge of this species ecology (Lizcano and Alvarez 2008;Merino and Rossi 2010).…”
Section: Discussionmentioning
confidence: 83%
“…1). The physical characteristics and mammalian biogeography of these systems has been considered in detail in recent studies (Molinari 2007;Anderson & Gutiérrez 2009;Anderson et al 2012;QuirogaCarmona & Molinari 2012;Gutiérrez et al 2015). A succinct description of these mountain systems, and the Venezuelan political divisions (within parentheses) from which we examined specimens, are: 1) Cordillera Oriental [de Colombia], on its Venezuelan side (Táchira, SW of the Táchira Depression; Apure); 2) Sierra de Perijá (or Molecular analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Their fossil record is scarce and thus, the validity of some of the species is doubtful (Alcaraz & Zurita, 2004;Menegaz, 2000;Merino & Rossi, 2010). So far, there are only few studies on extinct neotropical cervids and even fewer attempting to reconstruct the phylogeny of fossil and extant neotropical deer (Gutiérrez et al, 2015;Escobedo-Morales et al, 2016;Gutiérrez et al, 2017).…”
Section: Evolutionary Historymentioning
confidence: 99%
“…Gutiérrez et al (2015) tested whether the degree of concavity of the dorsal outline in lateral view and the shape of the lacrimal fossa can distinguish Mazama bricenii and Mazama rufina, but found that these characters are too variable to discriminate species. In the molecular and TE analyses here, Mazama bricenii was placed as the sister taxon to Mazama rufina, while in Gutiérrez et al (2015) and Gutiérrez et al (2017) Mazama bricenii was nested within Mazama rufina and the opposite was the case in Heckeberg et al (2016). Gutiérrez et al (2015Gutiérrez et al ( , 2017) stated based on their results that Mazama bricenii is not a valid taxon, but a junior synonym of Mazama rufina.…”
Section: Hippocamelusmentioning
confidence: 99%